The Islamic State: from terrorism to totalitarian insurgency - Filipec, Ondřej (Routledge, Taylor & Francis Group, 2020)
Examines the ideology of ISIS with a focus on radical Islamism and Salafi-jihadism. Explores the attitude of key state and non-state actors, especially Russia, USA and the Global Coalition, towards Daesh. An indispensable guide to the study of modern terrorism, this book will be of great interest to students and researchers of Middle East studies, terrorism, with a focus on ISIS, military and strategic studies, politics and international relations, as well as general readers --